2014
DOI: 10.1039/c3nr05431d
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate coated, folate functionalized colloidal graphene as a nanocarrier for both hydrophobic and hydrophilic drugs

Abstract: Although graphene based drug delivery has gained significant recent interest, the synthesis of colloidal graphene based nanocarriers with high drug loading capacities and with targeting ligands at the outer surface is a challenging issue. We have synthesized carbohydrate coated and folate functionalized colloidal graphene which can be used as a nanocarrier for a wide variety of hydrophobic and hydrophilic drugs. The synthesized colloidal graphene is loaded with paclitaxol, camptothecin, doxorubicin, curcumin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 44 publications
0
67
0
Order By: Relevance
“…The family of nanocarriers include polymer, nano-liposome, carbon nanomaterials, and gold nanoparticles [3][4][5][6][7], while some of them still have safety concerns [8][9][10][11]. In addition, the intracellular retention time of drugs loaded by these nanomaterials is transient [12][13][14][15][16], which harmers their translation into further biomedical application.…”
Section: Introductionmentioning
confidence: 98%
“…The family of nanocarriers include polymer, nano-liposome, carbon nanomaterials, and gold nanoparticles [3][4][5][6][7], while some of them still have safety concerns [8][9][10][11]. In addition, the intracellular retention time of drugs loaded by these nanomaterials is transient [12][13][14][15][16], which harmers their translation into further biomedical application.…”
Section: Introductionmentioning
confidence: 98%
“…The amphiphilic and planar structure of GO enable it to incorporate hydrophilic and/or hydrophobic biomolecules which gives the opportunity to prevent its instability in a medium [15, 18, 22]. In addition, the large surface area and oxygen-containing functional groups of GO such as phenol hydroxyl, epoxy, and carboxylic groups make it ideal for providing high drug loading efficiency, good dispersion, and easily functionalization [2, 23].…”
Section: Introductionmentioning
confidence: 99%
“…But, these nGO sheets were not stable in salt containing aqueous solution such as buffer or biological media. Normally, GO sheets are modified with polymers to increase their stability in the presence of salt and to use them for biological applications [9][10][11]13]. Pluronic F127 is a biocompatible tri-block copolymer which has been used to stabilize nGOs in biological solutions [14,26,27].…”
Section: Preparation and Surface Functionalization Of Ngomentioning
confidence: 99%
“…Several researchers have prepared folate conjugated GO and used them for targeted delivery of therapeutic drugs to the cancer cells [11,21,22]. Although it was observed that the cellular uptake of GO increased after folate conjugation, no systemic study on the effect of FA density on tumor targeting has been reported so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation